2011
DOI: 10.1167/iovs.10-5686
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Propagation of Mesenchymal Stem Cells from the Lacrimal Gland

Abstract: Murine lacrimal glands contain mesenchymal stem cells that seem to play a pivotal role in tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…Previous studies have shown that mesenchymal stem cells exist in both lacrimal glands [57] and pancreas, specifically in ductal regions [58]. Thus, it is possible that loss of P2X7 enhances the differentiation of mesenchymal progenitor cells toward the adipocyte lineage, resulting in increased adipocyte numbers in periductal regions of the pancreas and lacrimal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mesenchymal stem cells exist in both lacrimal glands [57] and pancreas, specifically in ductal regions [58]. Thus, it is possible that loss of P2X7 enhances the differentiation of mesenchymal progenitor cells toward the adipocyte lineage, resulting in increased adipocyte numbers in periductal regions of the pancreas and lacrimal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, You et al isolated the progenitor cells from the injured murine LG and identified them as mesenchymal stem cells. 16 They were not able to isolate progenitor cells from the uninjured murine LG. 16 We recently developed a method to culture MECs from uninjured, adult rat LGs.…”
mentioning
confidence: 99%
“…16 They were not able to isolate progenitor cells from the uninjured murine LG. 16 We recently developed a method to culture MECs from uninjured, adult rat LGs. 5 MECs typically take 3-4 weeks to differentiate.…”
mentioning
confidence: 99%
“…Fibroblasts appeared by the third week of culture. None of these obser vations had been registered in our previous experiments or reported by other authors in studies using shorter culture periods (10,17,18,21) . The use of a combination of quinolone (ofloxacin) and aminoglycoside (gentamicin) was effective in terms of preventing contamination of the culture.…”
mentioning
confidence: 63%